Variational Integrators for Higher Order Differential Equations (Journal of Computational Mathematics, 2003)
We analyze three one parameter families of approximations and show that they are symplectic in Lagrangian sense and can be related to symplectic schemes in Hamiltonian sense by different symplectic mappings. We also give a direct generalization of Veselov variational principle for construction of scheme of higher order differential equations. At last, we present numerical experiments.